ACOUSTO-OPTICS : Acousto-optic method of spatial frequency filtration based on diffraction of two eigenmodes of a crystal. (28th July 2017) - Kotov, V M; Averin, S V; Kuznetsov, P I; Kotov, E V
Abstract: A method is proposed for two-dimensional spatial frequency filtration based on acousto-optic (AO) diffraction of two eigenmodes of a crystal on a single acoustic wave. It is shown that AO filters, based on the use of such diffraction, ensure the enhancement of the two-dimensional image edge during its optical Fourier processing. The main theoretical conclusions are experimentally confirmed using an AO paratellurite filter.